Creating conditions for sustainable metropolitan nature system in Lodz - Urszula Krolikowska (European Regional Science Association (ERSA), 2010)
Lodz, the third of the largest cities in Poland, is inhabited by 745 000 of people and covers the area of 294 km². Today Lodz is transforming from the textile industry into the multifunctional metropolis. City authorities in collaboration with scientists from the European Regional Center on Ecohydrology under the auspices of UNESCO in Lodz, launched the project 'blue - green network'. Rationally planned ecological system that includes forests, parks and reservoirs, is being created in the concentrated settlement for recreation and improvement of the living conditions of citizens.
Keywords: 330